Geological investigations of Sulawesi (Celebes) before 1930 - van Gorsel, J.T. (Ikatan Ahli Geologi Indonesia, 2022)
This paper is an overview of the early discoveries of the geology of Sulawesi, from the first naturalist expeditions in the 1820s until the 1930s. Most of the contributions to the knowleddge of the geology of Sulawesi during the Dutch colonial era came between the late 1880s and 1930, after which geological and mining investigations essentially stopped for four-decades. Before Indonesian Independence in the 1940s, Sulawesi island had been called Celebes, a name introduced by Portuguese explorers in the early 1500s.Geographically, Sulawesi is rather unique among the larger islands of Indonesia. Unlike the other three large islands Sumatra, Borneo and Java, Sulawesi has four ‘arms’, which are all surrounded by deep seas, and virtually the entire island is mountainous terrain without major rivers or delta systems. Active volcanism is limited to the eastern half of the North Arm and the lone Una-Una volcano in the Tomini Gulf, while Miocene and recently extinct volcanoes are present in SW Sulawesi.Geologic exploration was challenging. Surveys into uncharted territories before 1920 (before the arrival of detailed topographic maps, air photos and satellite imagery), required topographic surveying of all itineraries with chain and compass, and with a barometer for estimating altitudes.